The centrality of health behaviours: A network analytic approach. Issue 1 (13th December 2018) - Nudelman, Gabriel; Kalish, Yuval; Shiloh, Shoshana
Abstract : Objectives: Since behavioural risk factors are the foremost causes of disability and premature mortality, developing new perspectives for understanding them is of utmost importance. This paper describes an innovative approach that conceptualizes health‐related behaviours as nodes in a weighted network. Design & Methods: Using self‐reported data from a representative sample ( n  =   374), a network of 37 health behaviours was analysed, with the aim of identifying 'central' nodes, that is, behaviours that are likely to co‐occur with others and potentially influence them. Results: In line with conservation of resources theory, the analysis indicated that behaviours related to basic physiological needs (nutrition and sleep) were most central. Behaviour centrality also varied across subpopulations: Periodic medical examinations, eating meals regularly, and sleep hygiene were more central among high‐ compared to low‐socio‐economic status participants; behaviours related to supportive social relationships and sun protection were more central among women compared to men. Conclusion: By emphasizing behavioural connectivity, the approach applied herein has identified core health behaviours with potentially high impact on healthy lifestyle behaviours. Statement of Contribution What is already known on this subject? Many health behaviours are related to each other. Engagement in one health behaviour can affect engagement in other behaviours. What does this study add? Health behaviour can be viewed and analysed as a network. Sleep and nutrition behaviours are the most central behaviours in the network. Centrality varies as a function of socio‐economic status and gender.